Colonized bodies, worlds transformed : toward a global bioarchaeology of contact and colonialism - Murphy, Melissa Scott; Klaus, Haagen D.; Larsen, Clark Spencer (Bioarchaeological interpretations of the human past., 2017)
"This book merges bioarchaeology and historical archaeology to examine changes to diet, mortuary practices, and diseases in post-fifteenth century colonialism from a global perspective"--Provided by publisher